Cathartic Ink: A Qualitative Examination of Tattoo Motivations for Survivors of Sexual Trauma. Issue 3 (3rd March 2020) - Maxwell, December; Thomas, Johanna; Thomas, Shaun A.
ABSTRACT: Prior research indicates that motivations for obtaining tattoos are generally to signify philosophical positions, identity formation, life transitions and group membership. However, questions remain around the generalizability of these motivations for special populations. The current study advances the extant literature by qualitatively examining a group of self-identified survivors of sexual violence and their motivations for obtaining tattoos. Results of our study indicate that survivors of sexual violence seek out tattoo as a non-traditional form of healing. Survivors sought out tattoos as a means of regaining control of their bodies and their environment, reclamation and anti-normative healing and deviance from the patriarchy.